Quality Administration as a Strategic Advantage for Schools: A Management Analysis to Enhance Educational Competitiveness - Nur Alif Abdul Kholik (Global Education Journal, 2026)
Quality education is able to improve the quality of human resources and the nation's competitiveness in the global era. However, many educational institutions currently face great challenges in maintaining quality stability due to administrative governance which is still considered as a mere archive, not a strategic function. Poor document and data management often leads to low accountability and loss of public trust. Therefore, a transformation is needed in the management of quality administration in order to be able to improve the bureaucracy into a real advantage for schools. This article aims to analyze the management strategy of education quality administration and its impact on improving the overall competitiveness of schools. This study uses a qualitative approach with a Systematic Literature Review (SLR) design. The data was collected through a search of scientific databases such as Google Scholar using Publish or Perish (PoP) software with the criteria of journal articles in the last five years. The data analysis techniques used are collecting data, presenting data, and inferring from relevant literature. The results of the study show that an effective quality administration management strategy is integrated in the POAC cycle (planning, organizing, mobilizing, and control), strategic administrative structuring, and harmonizing the digitization of information services. The use of technology has been proven to be able to minimize human error, which directly increases the perception of the professionalism of the institution in the eyes of the public. In conclusion, orderly and transparent administration is an absolute necessary condition in the implementation of Total Quality Management (TQM) to create quality schools. The implication of this study is the importance of school leaders to invest in human resource competencies and system digitalization to build public trust and ensure quality sustainability in the midst of increasingly fierce educational competition.